Pola makan, aktivitas fisik, gula darah, dan risiko luka kaki diabetik pada pasien diabetes melitus - Tuti Suprapti; Asep Aep Indarna (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by increased blood glucose (hyperglycemia). The prevalence of diabetes continues to increase until it reaches 578 million in 2030 and 700 million in 2045. Physical activity has an impact on insulin action in people at risk of diabetes mellitus. Lack of activity is one of the factors that plays a role in causing insulin resistance, Purpose: To analyze diet patterns, physical activity, and the risk of diabetic foot injuries in diabetes mellitus patients. Method: Descriptive analytical research using the sampling technique is accidental sampling, with a total sample of 40 DM patients without wounds. The instruments used were questionnaire sheets in the form of eating patterns and physical activity with international physical activity questionnaire (IPAQ) measuring instruments and blood sugar measuring instruments. The analysis used in this research is univariate analysis. Results: As many as 82.5% of blood sugar was controlled at 100-199 mg/dl, 90% of sufferers had a risk of injury using footwear, 75% felt heat in their feet, 95% felt their pulse in their feet was weak and irregular. The food frequency questionnaire (FFQ) consists of 28 staple foods in the form of white rice with a frequency of 4-6 times/day, 40%, fresh fish, and 42.5% consume meat with a frequency of 1-3 times/week, so it is necessary to take precautions to prevent neuropathy. . Conclusion: The type and amount of food greatly influences the incidence of DM, so assessment and screening of food patterns needs to be carried out. Apart from that, DM sufferers need to increase physical activity according to their abilities and the assessment of injury risk needs to be improved to prevent neuropathy. Suggestion: Health workers need to increase education about wound care, early detection of the risk of diabetic foot wounds, and carrying out physical activities such as foot exercises. Keywords: Blood Sugar; Diabetes Mellitus; Physical Activity; Wound Prevention. Pendahuluan: Diabetes melitus (DM) merupakan penyakit gangguan metabolisme kronis yang ditandai peningkatan glukosa darah (hiperglikemi). Prevalensi diabetes terus meningkat hingga mencapai 578 juta pada 2030 dan 700 juta di tahun 2045. Aktivitas fisik berdampak terhadap aksi insulin pada orang yang berisiko diabetes melitus. Kurangnya aktivitas merupakan salah satu faktor yang ikut berperan yang menyebabkan resistensi insulin, Tujuan: Untuk menganalisa pola makan, aktivitas fisik, dan risiko luka kaki diabetik pada pasien DM. Metode: Penelitian deskriptif analitik menggunakan teknik pengambilan sampel adalah accidental sampling, dengan jumlah sampel 40 pasien DM tanpa luka. Instrumen yang digunakan lembar kuesioner berupa pola makan dan aktivitas fisik dengan alat ukur international physical activity questionnaire (IPAQ) dan alat ukur gula darah. Analisis yang digunakan dalam penelitian ini adalah analisis univariat . Hasil: Sebanyak 82.5% gula darah terkontrol 100-199 mg/dl, risiko terjadinya luka 90% penderita menggunakan alas kaki, 75% merasakan panas pada kaki, 95% merasakan denyut nadi sedang di kaki. Food frekuensi quesionere (FFQ) sebanyak 28 makanan pokok berupa nasi putih dengan frekuensi 4-6 kali/hari, 40% ikan segar, dan 42.5% mengkonsumsi daging dengan frekuensi 1-3 kali/minggu, sehingga perlu dilakukan pencegahan agar tidak terjadi neuropati. Simpulan: Jenis dan jumlah makanan sangat berpengaruh terhadap kejadian DM, sehingga pengkajian dan screening pola makanan perlu dilakukan. Selain itu, penderita DM perlu meningkatkan aktivitas fisik sesuai kemampuan dan pengkajian risiko luka perlu ditingkatkan untuk mencegah terjadinya neuropati. Saran: Petugas kesehatan perlu meningkatkan edukasi tentang perawatan luka, deteksi dini risiko luka kaki diabetik, dan dilakukannya aktivitas fisik seperti senam kaki. Kata Kunci: Aktivitas Fisik; Diabetes Melitus; Gula Darah; Pencegahan Luka.